Çağdaş Mimari Yapılarda Seramik Panolar Ve Yıldız Teknik Üniversitesi Kongre Ve Kültür Merkezi Uygulaması - Gül, Saliha Nesli; Özkeçeci, İlhan; Alacalı, Hakan (The Turkish Online Journal of Design Art and Communication, 2014)
Ceramic panels which are produced for decorative purposes, constitute an integral part of architectural design. The use of ceramic in architectural buildings which can be dated back to the Seljuks period in Turkey, especially the productions of ceramics after 1950 go on until today with modernist approaches. Ceramic panel practices mostly take place in the inner and outer surfaces of cultural centres, hotels, company, religious and social buildings and structures. In this article, samples in contemporary architecture of ceramic panel practices are examined in detail including composition designs and surface patterns of ceramic panels. As in the category of modern ceramic practices, artworks of Jale Yilmabasar, Fureya Koral, Sadi Diren, Beril Anilanmert, Mustafa Tuncalp and Bedri Rahmi Eyuboglu are analyzed in terms of aesthetics. In this study, by analyzing the examined ceramic panels practices, ceramic panel practices in YTU Congress and Culture Centre is produced in a modernist style, reflecting the original methods including the aesthetic and design process of the practices is evaluated.
Keywords: Çağdaş Mimaride Seramik; Mimari ve Seramik İlişkisi; Seramik Duvar Panoları; YTÜ Kongre ve Kültür Merkezi.; Ceramic in Contemporary Architecture; The Relationship Betwwen Architecture and Ceramic; Ceramic Panels; YTU Congress and Culture Centre